Variation in communication satisfaction of academic staff in universities in Yemen depending on national culture - Al-Nashmi, Murad Mohammed; Zin, Syd Abdul Rahman Hj Syd (Emerald Group Publishing Limited, 2011)
Purpose The purpose of this study is to provide an assessment of communication practices in universities in Yemen. The paper also gives further insight into the relationship between national culture (NC) and communication satisfaction (CS) of multicultural teams at universities. Design/methodology/approach The study used a quantitative research design and used quantitative instruments to collect data from 338 faculty members from different countries including professors, associate professors, assistant professors, teachers, and tutors working at four universities in Yemen. Data were collected using the CS questionnaire and the Value Survey Module. Findings The analysis of the data shows that the CS levels among the academic staff vary according to the nationality. In addition, analysis of the data revealed that there is a significant relationship between CS factors and NC dimensions. Originality/value This research provides valuable insight into the faculty members' development and performance. It may assist the multicultural academic staff to be able to help, improve working relationships, and understanding of intercultural communication which help them to reach a CS.